2014
DOI: 10.1891/1058-1243.23.1.17
|View full text |Cite
|
Sign up to set email alerts
|

Major Survey Findings of Listening to MothersSM III: New Mothers Speak Out

Abstract: To understand the experiences and views of childbearing women in the United States and trends over time, Childbirth Connection carried out the third national Listening to Mothers survey among 2,400 women who gave birth in U.S. hospitals to a single baby from mid-2011 to mid-2012 and could participate in English. A follow-up survey directed to the same participants explored postpartum experiences, in depth and well into the second year after birth; views about maternity care; and some additional pregnancy and b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
140
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(153 citation statements)
references
References 0 publications
5
140
1
7
Order By: Relevance
“…It is important to educate parents on how to share a bed safely, as parents have stated they would appreciate this advice 42 and because bedsharing is widespread. 10,[44][45][46] Public health efforts must address the reality that tired parents must feed their infants at night somewhere and that sofas are highly risky places for parents to fall asleep with their infants, especially if parents are smokers or under the influence of alcohol or drugs. Safe sleep messages must also recognize that breastfeeding infants and formula-feeding infants do not sleep the same way and do not share the same risks when bedsharing.…”
Section: Future Directionsmentioning
confidence: 99%
“…It is important to educate parents on how to share a bed safely, as parents have stated they would appreciate this advice 42 and because bedsharing is widespread. 10,[44][45][46] Public health efforts must address the reality that tired parents must feed their infants at night somewhere and that sofas are highly risky places for parents to fall asleep with their infants, especially if parents are smokers or under the influence of alcohol or drugs. Safe sleep messages must also recognize that breastfeeding infants and formula-feeding infants do not sleep the same way and do not share the same risks when bedsharing.…”
Section: Future Directionsmentioning
confidence: 99%
“…1 However, when compared with IAFHR, EFM does not reduce the overall risk of perinatal death (relative risk [RR] = 0.85; 95%; confidence interval [CI], 0.59-1.23) or cerebral palsy (RR = 1.74; 95% CI, 0.97-3.11). Electronic fetal monitoring was associated with reduction in the rate of neonatal seizures by half (RR = 0.50; 95% CI, 0.31-0.80); however, this reduction was not ultimately associated with differences in long-term neonatal neurologic status.…”
Section: Introductionmentioning
confidence: 99%
“…27 The Internet is an even more common source of information, and 97% of mothers reported that they used the Internet for this purpose. 1 Nurses and other maternity care providers should be aware of the content of Web sites and books on childbirth to assist women in their care to make informed decisions. We evaluated evidence-based information available to consumers in 3 different types of Web sites: popular maternity sites; maternity provider sites; and childbirth education sites and popular maternity books.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in maternal demographics and risk factors such as increased maternal age during the first pregnancy have been proposed as potential causal mechanisms to explain high CB utilization, but research has now shown that these are not root causes [3] . Alternately, more recently CB has been linked to the increased use of commonly used clinical interventions for labor management such as continuous electronic fetal monitoring (CEFM), epidural analgesia, and oxytocin for induction or augmentation of labor.…”
Section: Introductionmentioning
confidence: 99%